Construction of Yunnan Ethnic Minority Music in Popular Singing Major Courses in Yunnan Provincial Universities (Journal of Namibian Studies : History Politics Culture, 2023)
The construction of courses in the popular singing major in Yunnan provincial universities should fully utilize the resources of Yunnan ethnic minority music, geographical and cultural advantages, to cultivate outstanding popular professionals with distinct personalities and ethnic characteristics. In the construction of courses in the popular singing major in Yunnan provincial universities, it is necessary to strengthen the construction of the teaching staff, the setting of teaching materials, and the development of local talent to create a distinctive teaching model and clarify the discipline positioning and development direction. At the same time, it is important to strengthen the awareness of ethnic minority music culture and cultivate cultural confidence. Emphasis should be placed on the development of artistic practice and the establishment of practice bases to create high-quality courses. Promoting the diversified development of Yunnan-localized popular vocal works and professionals in the field of popular music, further achieving effective breakthroughs and innovative development in the construction of courses in Yunnan ethnic minority music in the popular singing major in Yunnan provincial universities.